Ответ:
a = 10/9 b = 1/72
Пошаговое объяснение:
[tex]( \frac{1}{15} + \frac{7}{45} ) \div \frac{1}{5} [/tex]
[tex]( \frac{3}{45} + \frac{7}{45} ) \div \frac{1}{5} [/tex]
[tex] \frac{10}{45} \div \frac{1}{5} [/tex]
[tex] \frac{10}{45} \times \frac{5}{1} [/tex]
[tex] \frac{10}{9} \times \frac{1}{1} = \frac{10}{?9} [/tex]
[tex]( \frac{3}{4} - \frac{2}{3} ) \div 6[/tex]
[tex]( \frac{9}{12} - \frac{8}{12} ) \div \frac{6}{1} [/tex]
[tex] \frac{1}{12} \times \frac{1}{6} = \frac{1}{72} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
a = 10/9 b = 1/72
Пошаговое объяснение:
[tex]( \frac{1}{15} + \frac{7}{45} ) \div \frac{1}{5} [/tex]
[tex]( \frac{3}{45} + \frac{7}{45} ) \div \frac{1}{5} [/tex]
[tex] \frac{10}{45} \div \frac{1}{5} [/tex]
[tex] \frac{10}{45} \times \frac{5}{1} [/tex]
[tex] \frac{10}{9} \times \frac{1}{1} = \frac{10}{?9} [/tex]
[tex]( \frac{3}{4} - \frac{2}{3} ) \div 6[/tex]
[tex]( \frac{9}{12} - \frac{8}{12} ) \div \frac{6}{1} [/tex]
[tex] \frac{1}{12} \times \frac{1}{6} = \frac{1}{72} [/tex]